1990
DOI: 10.1063/1.103325
|View full text |Cite
|
Sign up to set email alerts
|

Effect of impurities on the thermal oxidation process in InP

Abstract: Sulfur (n-type) and zinc (p-type) doped and undoped InP have been thermally oxidized in the temperature range 400 °C≤T≤600 °C. The Raman scattering and Auger electron spectroscopy techniques show that the doping enhances the formation of the crystalline InPO4 phase and favors the growth of crystalline phosphorus at the oxide/InP interface.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

1991
1991
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 8 publications
1
2
0
Order By: Relevance
“…This result is consistent with the previous studies where some degree of crystallization of InP surface oxides has been found, in particular, at elevated temperatures [27]. Our results indicate that some crystallization occurs even without any annealing, which is further consistent with the theoretical prediction about the formation of coherent InPO 4 /InP [57].…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…This result is consistent with the previous studies where some degree of crystallization of InP surface oxides has been found, in particular, at elevated temperatures [27]. Our results indicate that some crystallization occurs even without any annealing, which is further consistent with the theoretical prediction about the formation of coherent InPO 4 /InP [57].…”
Section: Resultssupporting
confidence: 93%
“…Namely, after the NH 3 exposure of p-InP at 400 • C, PL signal remained the same while the lower nitridation temperature of 20 • C-300 • C even decreased the PL signal to 2/3 approximately for p-InP. The reason(s) for this difference between n-InP and p-InP is not clear at the moment, however, the doping has been also previously found to cause changes in the InP surface properties [27]. Furthermore, if the native oxide of p-InP includes Zn-O bonding, the N incorporation into ZnO nanostructures might cause defect levels, as found previously [70].…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation